Effect of acorn (Quercus robur) intake on faecal egg count in outdoor reared black Slavonian pig - Salajpal, Krešimir (Acta agriculturae slovenica. Suplement, 2004)
Chemical composition of the acorn (Quercus robur), tannin content and its ability to influence the faecal egg count output reduction in the Black Slavonian Pig reared in outdoor production system were investigated. A total of 20 Black Slavonian Pigs with naturally acquired parasite were randomly divided into experimental (E) and control (C) group. The pigs in experimental group were fed an acorn Ad libitum and the pigs of the control group were given only 2 kg of concentrate. The faecal egg count (FEC) was assessed by individual pig before and after acorn consumption. Faecal egg count reduction percentage (FECR%) was calculated separately for large roundworm (Ascaris suum) and other gastrointestinal parasites (Oesophagostomum spp., Strongyloides and Hyostrongylus sp.). The results demonstrate that acorn is tannin rich forage (65.6 g kg-1) which can reduce FEC output of pigs parasitised with gastrointestinal nemathodes. The reduction in total faecal egg count output in acorn fed pigs was 96.01%. FECR% for A. suum and other nematodes of the gastrointestinal tract (Oesophagostom spp., Strongyloides and Hyostrongylus sp.) was 96.56% and 93.55%, respectively. These results would imply that the gastrointestinal nematode population was highly sensitive and responsive to the effect of acorn tannin in feed. Therefore, the acorn grazing has the potential of aiding in the control of the gastrointestinal parasites in the outdoor reared Black Slavonian Pig and consequently results in reduced need for anthelmintic treatment.
Keywords: krma; pasme; prašiči; reja